Analysis of The Failure Protection System 20 KV CBO T75B Substation Malibu Feeder PT PLN (Persero) UP3 Menteng - Mukti, Doni Abdul; Sudiarto, Budi (Syntax Literate, 2021)
Protection is a safety in the electric power system installed in the electric power distribution system, power transformer, electric power transmission, and electric generator used to secure the power system electricity from electrical disturbances or overloads by separating the disturbed parts of the electric power system from the undisturbed electrical power system so that the undisturbed electrical system can continue to work. The protection system at the T75B substation has a work failure where when there is a short circuit on the consumer side, it causes the PMT (Power Breaker) for the Malibu Feeder at the Kebon Sirih Substation to trip while the CBO (Circuit Breaker Outgoing) cubicle at the T75B substation does not trip. This resulted in an unexpected widespread blackout. To find out the cause of the failure of the protection system, several tests and analyzes were carried out, namely protection design testing, protection relay coordination testing, protection system construction analysis, protection equipment performance testing. It is hoped that the test results can be used as a reference for improvement so that similar failures do not recur.